NF-κB and Angiogenesis Inhibitors from the Aerial Parts of Chresta martii - Queiroz, Marcos Marçal Ferreira; Monteillier, Aymeric; Berndt, Sarah; Marcourt, Laurence; Franco, Eryvelton De Souza; Carpentier, Gilles; Nejad Ebrahimi, Samad; Cuendet, Muriel; Bolzani, Vanderlan Da Silva [UNESP]; Maia, Maria Bernadete Souza; Queiroz, Emerson Ferreira; Wolfender, Jean-Luc (American Chemical Society (ACS), 2018)
The ethyl acetate extract of the aerial parts of Chresta martii showed significant in vitro NF-κB inhibition. Bioactivity-guided isolation was undertaken using HPLC microfractionation to localize the active compounds. Different zones of the HPLC chromatogram were linked to NF-κB inhibition. In parallel to this HPLC-based activity profiling, HPLC-PDA-ESI-MS and UHPLC-TOF-HRMS were used for the early identification of some of the compounds present in the extract and to get a complete phytochemical overview. The isolation of the compounds was performed by high-speed counter-current chromatography and further semipreparative HPLC. Using this approach, 14 compounds were isolated, two of them being new sesquiterpene lactones. The structures of the isolated compounds were elucidated by spectroscopic methods including UV, ECD, NMR, and HRMS. All isolated compounds were evaluated for their inhibitory activity of NF-κB and angiogenesis, and compound 2 showed promising NF-κB inhibition activity with an IC50 of 0.7 μM. The isolated compounds 1, 2, 5, 7, and 8 caused a significant reduction in angiogenesis when evaluated by an original 3D in vitro angiogenesis assay.